2020
DOI: 10.1002/app.49963
|View full text |Cite
|
Sign up to set email alerts
|

Effect of special structure of clam shell powder on structure and properties of castor oil‐based composites

Abstract: Castor oil (CO) is an environmentally friendly renewable green resource and ideal alternative to petroleum resources. The preparation of high strength and high toughness castor oil-based polyurethane prepolymer (COPU) composites has significant applications such as supporting material and engineering plastic sheet. In this study, unmodified clam shell powder (CSP) with a unique CaCO 3-proteoglycan structure was used as a filler to prepare compatible reinforced COPU composite materials. Investigation of the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…However, more signs of wood powder shedding could be observed on the fractured interfaces shown in Figure 2(C) and (D) for WUF and WPW, respectively, implying that the interfacial interaction force between WF and PP or COPW was relatively weak. These phenomena may be due to the fact that the abundant ─OH groups in WF could only form urethane bond with the ─NCO group in COPU, [11,12,15,17] and also form a hydrogen bond with the ─NH in UF. Consequently, no urethane bond formation could occur between WF and PP or COPW.…”
Section: Water Absorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, more signs of wood powder shedding could be observed on the fractured interfaces shown in Figure 2(C) and (D) for WUF and WPW, respectively, implying that the interfacial interaction force between WF and PP or COPW was relatively weak. These phenomena may be due to the fact that the abundant ─OH groups in WF could only form urethane bond with the ─NCO group in COPU, [11,12,15,17] and also form a hydrogen bond with the ─NH in UF. Consequently, no urethane bond formation could occur between WF and PP or COPW.…”
Section: Water Absorptionmentioning
confidence: 99%
“…Inspired by these reports, [11,12] COPU and wood flour were melt-blended [13] with an internal mixer, and then the obtained material was used to prepare WF-based composite materials with a hot press. It is worth noting that up to 70 wt% of WF biomass was added to COPU for modification so as to make full use of biomass raw materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the low efficiency associated with using conventional compatibilizers and coupling agents, our research group has found that using polyurethane prepolymers as a compatibilizer can effectively improve the interfacial compatibility of biomass and polymers with high efficiency. [16][17][18] The high efficiency associated with polyurethane prepolymers is due to the reactivity of NCO terminal groups with polyhydroxy groups in biomass to form covalent bond, as well as physical cross-linking between the soft segments in polyurethane prepolymers and the polymer materials. The formation of chemical bonds and physical cross-links within the composites contribute to improving the interfacial compatibility of the materials.…”
Section: Introductionmentioning
confidence: 99%